Proprietary Law Schools and the Marketization of Access to Justice - Tejani, Riaz (Social Science Research Network, 2016)
The rise of for-profit law schools in the United States highlights the interplay of political and moral economy in the reproduction of legal expertise. This article offers ethnographic evidence from one ABA-accredited for-profit law school pseudonymously labeled New Delta School of Law. The article posits New Delta as a case study in market fundamentalism of the kind first theorized by Hungarian economist Karl Polanyi. Polanyi defined global capital as a “double movement” between free marketeerism on the one hand and countervailing social protectionism on the other. Treating this as incomplete, social philosopher Nancy Fraser has since argued that the emancipatory new social movements form a third element in what should more properly be considered a “triple movement.” In this article, I argue that for-profit law schools such as New Delta support Fraser’s revision. Drawing in capital commitments from large institutional investors with promises of high returns on the basis of guaranteed federal student loan dollars, New Delta recruits disproportionately from minority and low-income communities while offering low chances of bar passage and legal employment. By marrying free marketeerism with the discourse of emancipation, the school has successfully evaded scrutiny.
Law; Legal Studies
Keywords: anthropology; economic; finance; law; legal education; markets; morals; neoliberalism; race; regulation; triple movement

A Crisis of Executive Managerialism in the EU: No Alternative? - Joerges, Christian; Weimer, Maria (Social Science Research Network, 2012)
Against a backdrop of rapidly evolving crisis management in the European financial and sovereign debt crisis this essay aims both to explore and to re-consider the role of law in the EU integration process: What did law accomplish? Where did it fail? What is law going to endure? What kind of future can it envisage? The essay traces back the evolution of the law-politics relationship in both EU legal scholarship and practice from the foundational period of ‘integration-through-law’ to the advent of ‘new governance’ in the EU, and finally to the current deep transformations of EU law in new economic governance and the financial crisis. The centrality of law as ‘both the object and the agent’ of European integration, and the legal enshrinement of EU’s economic constitution has recently neglected the weight of ‘the social’ in the societies of post-war Europe, a failure which was to become detrimental to both domestic social stability and the legitimacy of integration. Attempts to cure Europe’s social deficit by re-conceptualizing the notion of law as new governance have widened the theoretical perspective of EU legal scholarship. Yet new governance has not delivered more social democracy and justice in Europe in practical terms, and continues to suffer from the methodological problems of its ‘definition-by-contrast.’ These problems re-emerge in current new economic governance, which Europe’s crisis management is generating. This hybrid arrangement of hard and soft law instruments has, to date, been economically unsuccessful and socially disastrous, especially in the South of Europe. Equally disquieting, the notion of democratic law (either in traditional or experimentalist understandings) has been replaced by a praxis of authoritarian executive managerialism. The essay concludes by sketching out an alternative understanding of law-mediated legitimacy in the integration process, namely ‘conflicts-law constitutionalism’. This approach stresses the normative value of conflicts and pluralism in the process of European integration. Instead of ‘ever more Europe’ it aims to secure the existing democratic credentials of EU law, namely its ability to correct the democratic deficit of the Member States while respecting their constitutional integrity.
Law
Keywords: EU economic constitution; EU financial crisis; European Union; governance; unity in diversity

Polanyi's Embeddedness and Shareholder Stewardship: A Contextual Analysis of Current Anglo-American Perspectives on Corporate Governance - Talbot, Lorraine E. (Social Science Research Network, 2012)
Polanyi saw the economy as properly embedded in society and argued that the capitalist free market, in commodifying social relations of production, seeks to disembed the economy from society. The resulting lack of continuity between society and economy, he maintained, created conflict which necessarily required state intervention. The market economy, therefore, in contrast to neoclassical/neoliberal economics’ vision of an autonomous, self-regulating market, required more, not less, state intervention to sustain it than alternative, more embedded economies. This article explores this conflict in the context of a specific neoliberal claim: that institutional shareholders are capable of being good “stewards” of the companies in which they invest. Utilising Polanyi’s embeddedness, this article assesses the “stewardship” approach as it is manifested in the US and in the UK. This approach is posited on a vision of a disembedded, self-regulating market. Putting it into practice is thus a retrograde step which will only exacerbate the problems created by the market-based corporate governance strategies which have prevailed since the late 1970s onwards.
Law
Keywords: Polanyi; conflict; crisis; embeddedness; shareholder stewardship

The Idea of a Three-Dimensional Conflicts Law as Constitutional Form - Joerges, Christian (Social Science Research Network, 2010)
‘Constitutionalisation’ is the key concept in the search for legitimate governance in the European Union and in the international system. This paper suggests the revitalising of a discipline which is widely neglected in European law and international law scholarship. It does not, however, recommend a return to the conflict of laws (private international law) in the traditional sense. The new type of conflicts law that the paper advocates is not concerned with selecting the proper legal system in cases with connections to various jurisdictions. This conflicts law is conceptualised as a response to the increasing inter-dependence of formerly more autonomous legal orders and to the democracy failure of constitutional states which result from the external effects of their laws and legal decisions on foreign systems and on their citizens who cannot understand themselves as their authors. European law has a vocation and many means both to compensate for the democracy failures of member states and to build upon this potential in its constitutionalisation. The conflicts law approach also provides new, albeit more restrained, perspectives at international level. WTO law is used to explore and document its constitutional perspectives. The conflicts law approach is differentiated into three dimensions. With this differentiated fabric, the approach responds to transformation processes which have affected contemporary law at all levels of governance after the rise of regulatory politics and the turn to governance. In its second dimension, conflicts law seeks to constitutionalise co-operative problem-solving under the lead of administrative bodies, while its third dimensions is concerned with both the recognition and the supervision of transnational governance arrangements and para-legal regimes.
Law; Sociology
Keywords: BLOCK; Fred; Europeanisation; World Trade Organization (WTO); always socially embedded' economy; constitutionalisation; deliberative democracy; economic law; economic sociology; multilevel governance; private international law; rule of law; social embeddedness; social regulation; supranationalism

Conflict of Laws as Constitutional Form: Reflections on International Trade Law and the Biotech Panel Report - Joerges, Christian (Social Science Research Network, 2007)
Hardly anywhere is the trend towards a perfection of transnational governance arrangements and their “legalization” more visible than in international trade. Governance arrangements established through and alongside WTO law are both practically important and theoretically challenging. They do not just organise international trade relations. They also affect national and regional (European) regulatory policies partly directly, partly more indirectly. How can we explain and how should we evaluate their emergence? The WTO system of 1994, which replaced the GATT of 1947, responded to the ever increasing importance of non-tariff barriers to trade. These barriers reflect regulatory concerns especially in the fields of health and safety, consumer and environmental protection. There importance for WTO member is such that they cannot simply be abandoned for the sake of free trade. This is why the responses the new international trade system institutionalised by special agreements concerning on-tariff barriers to free trade such as the Agreement on the Application of Sanitary and Phytosanitary Measures (SPS) and the Agreement on Technical Barriers to Trade (TBT) reflect a politicisation of international trade. Can we conclude that international markets have been re-regulated and that international trade law ensures their “social embeddedness”? The paper seeks yardsticks for an answer to these questions in the debates on transnational constitutionalism. It submits that constutionalisation can and should be based on a conflict-of approach. For its elaboration of this suggestion, the paper first contrasts the jurdification of transnational governance at the European and the international level. It then discusses the WTO panel report on the Biotech dispute. It concludes that the legalisation and judicialisation in that case have remained “thin.” What can be observed is a political rather than a social and legal embeddedness of markets.
Law; Political Science
Keywords: FOUCAULT; Michel; 1926-1984; Polanyi and Foucault; World Trade Organization (WTO); constitutionalisation; economic law; embeddedness; european governance; international trade; legal embeddedness; legalization; legitimacy; multilevel governance; national autonomy; risk regulation; social embeddedness; transnational governance

'Social Market Economy' as Europe's Social Model? - Joerges, Christian; Roedl, Florian (Social Science Research Network, 2004)
Europe continues to search for its - "European" - social model and the search seems to become increasingly urgent. It is no longer just the "democratic deficit", but also and alongside it, the "social deficit" of the EU which needs to be cured. That new concern is, in fact, a rejection of the older answers. According to the ordo-liberal interpretation of the European legal order as an "Economic Constitution" and, successively, in the analyses of the EU as a "Regulatory State", the sphere of social policy was to remain a domain of the nation state. This seems to have become impossible. The Constitutional Treaty, indeed, makes a new commitment: "The Union shall work for a Social Market Economy". This paper submits that this commitment is conceptually a failure, and politically not credible. The Convention preparing the Constitutional Treaty has apparently ignored the meaning of the concept in the form in which it was shaped in Germany's post-war period. This history entails some pitfalls for the Convention's intentions, as the German "Social Market Economy" involved not only a claim of integrating social concerns into the market economy, but also served to restrict claims for instruments of social policy remarkably at the same time. Moreover, the Convention has failed to confer a new and independent content to the concept of the "Social Market Economy", which could help to overcome the concept's ambivalent history, as well as the Union's real "social deficit". The few innovations, the Charter's Fundamental Social Rights and the Open Method of Co-ordination, were incorporated in such modest and non-committal forms that their potential to further the case for "social Europe" seems marginal. The paper concludes that the invocation of the "Social Market Economy" in the Constitutional Treaty is conceptually flawed and is politically an all too risky promise which may raise expectations which it will subsequently fail to deliver.
Law; Political Science
Keywords: constitution building; economic law; economic policy; governance; social deficit; social market economy; social policy